A Stone Can Bounce on the Surface of Water: A Conceptual Physics Analysis Study of Students - Wattimena, Herman Semuel; Jamaludin, Jamaludin; Batlolona, John Rafafy (Pascasarjana, Mataram University, 2024)
Throwing a stone on the surface of the water has been a popular hobby for thousands of years, but in recent times, this phenomenon is rarely encountered in physics education. Flat and round stones are the best choice due to their favorable surface area, which creates a rebound when they collide with the water. However, the